Workers' skill level and information technology: evidence from German service firms - Martin Falk; Katja Seim (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
This paperanalyses the link between human capitaland information technology(IT ) in the service production process. The analysis is based on 1994 cross-sectional data for 1929 German. Firms drawn from the first wave of the Mannheim Service Innovation Panel (MIP-S). Factor demand functions are used to analyse the determinants of the Firm-specific skillstructure. The empirical evidence indicates that firms with a higher IT investment to sales ratio employ a larger fraction of high-skilled workers. The relationship between IT investment and medium-skilled labour is rather weak while the unskilled labourshare is negatively related to the IT investment to sales ratio. U sing a translog production function to assess the productivity of different input factors, we find that human and informationcapital provide the most powerful contributions to output in the service sector.
Keywords: L8; O33; J23; 330; Information technology; skills; labour demand; service sector; Dienstleistungssektor; Produktionsfunktion; Computergestütztes Verfahren; Informationstechnik; Hochqualifizierte Arbeitskräfte; Humankapital; Arbeitsnachfrage; Schätzung; Deutschland